The Waring-Girard formulas for symmetric polynomials on spaces _p - Handera-Kalynovska, O.V.; Kravtsiv, V.V. (Carpathian Mathematical Publications, 2024)
Classical Waring-Girard formulas gives a representation of elementary and complete symmetric polynomials through the power symmetric polynomials. In this paper, we propose some analogs of the Waring-Girard formulas in the case of spaces _p, where 1p<∞, and show an application of obtained formulas in combinatorics.